The Low-Diversity Fecal Microbiota of the Critically Endangered Kākāpō Is Robust to Anthropogenic Dietary and Geographic Influences - Perry, Elena K.; Digby, Andrew; Taylor, Michael W. (Frontiers in Microbiology, 2017)
The critically endangered kākāpō, an herbivorous parrot endemic to New Zealand, is subject to intensive management to increase its population size. Key aspects of the management program include supplementary feeding and translocation of kākāpō between different predator-free islands to optimize the genetic composition of the breeding populations. While these practices have helped boost the kākāpō population, their impact on the kākāpō fecal microbiota is uncertain. Previous studies have found that the kākāpō possesses a low-diversity fecal microbiota, typically dominated by Escherichia/Shigella spp. However, the question of whether the low diversity of the kākāpō fecal microbiota is an inadvertent consequence of human interventions has yet to be investigated. To that end, we used high-throughput Illumina sequencing of 16S rRNA gene amplicons obtained from fecal material of 63 kākāpō representing different diets, islands, and ages. Remarkably, neither supplementary feeding nor geographic location were associated with significant differences in the overall fecal microbial community structures of adult kākāpō, suggesting that the kākāpō’s low-diversity fecal microbiota is both inherent to this species and robust to these external influences.